1996
DOI: 10.1111/j.1525-1594.1996.tb04538.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Platelet, Granulocyte, and Complement Activation During Cardiopulmonary Bypass Using Heparin‐coated Equipment

Abstract: The effects of heparin-coated cardiopulmonary bypass (CPB) systems on platelet, granulocyte, and complement activation were investigated during cardiopulmonary bypass. Thirty patients underwent coronary artery bypass surgery with a heparin-coated (Carmeda Bio-Active Surface, CBAS, Medtronic, U.S.A.) CPB system (HC group, n = 10), a heparin-coated oxygenator and uncoated CPB circuit (HO group, n = 10), or an uncoated system (UC group, n = 10). In the HO group, plasma C3a (1667 +/- 632 ng/ml) and C4a (1088 +/- 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 22 publications
1
43
0
Order By: Relevance
“…Thus, they have concluded that granulocytes may be activated through complement activation [10]. They did not, however, directly examine the correlation between C3a and GEL concentrations at different time points after protamine administration.…”
Section: Commentmentioning
confidence: 88%
See 3 more Smart Citations
“…Thus, they have concluded that granulocytes may be activated through complement activation [10]. They did not, however, directly examine the correlation between C3a and GEL concentrations at different time points after protamine administration.…”
Section: Commentmentioning
confidence: 88%
“…The GEL concentration has been reported to be significantly lower in heparin-coated circuits, as compared to uncoated circuits [6,10,11]. The low level of GEL concentration at 60 min after CPB initiation is probably due to this inhibitory effect exerted by heparincoated circuits.…”
Section: Commentmentioning
confidence: 94%
See 2 more Smart Citations
“…Most in vitro or animal models demonstrate benefits of heparin coating including reduced soluble thrombin production, platelet binding, and D-dimer production [12,[15][16][17][18][19]20]. With respect to inflammation, most studies demonstrate reduced inflammatory response, particularly in the interleukins, alternative complement pathway and polymorphonuclear cells, compared to controls and other coating systems [12,[20][21][22][23][24][25]26].…”
Section: Heparinmentioning
confidence: 99%